2009
DOI: 10.1074/jbc.m109.036376
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis of Light Harvesting and Photoprotection in CP24

Abstract: CP24 is a minor antenna complex of Photosystem II, which is specific for land plants. It has been proposed that this complex is involved in the process of excess energy dissipation, which protects plants from photodamage in high light conditions. Here, we have investigated the functional architecture of the complex, integrating mutation analysis with time-resolved spectroscopy. A comprehensive picture is obtained about the nature, the spectroscopic properties, and the role in the quenching in solution of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
98
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(109 citation statements)
references
References 64 publications
7
98
0
Order By: Relevance
“…The pigment binding of most of the complexes was studied with the use of mutation analysis. Mutations of the putative Chl-binding residues followed by in vitro reconstitution [90] has led to the production of complexes lacking individual chromophores, allowing the characterization of each chromophore in each binding site [91][92][93][94][95][96]. This analysis has revealed that the biochemical and spectroscopic properties of Chls in several of the binding sites are conserved across the Lhc family.…”
Section: Structure Of the Antenna Complexes Of Photosystem IImentioning
confidence: 99%
See 2 more Smart Citations
“…The pigment binding of most of the complexes was studied with the use of mutation analysis. Mutations of the putative Chl-binding residues followed by in vitro reconstitution [90] has led to the production of complexes lacking individual chromophores, allowing the characterization of each chromophore in each binding site [91][92][93][94][95][96]. This analysis has revealed that the biochemical and spectroscopic properties of Chls in several of the binding sites are conserved across the Lhc family.…”
Section: Structure Of the Antenna Complexes Of Photosystem IImentioning
confidence: 99%
“…For example, the four Chl-binding sites located in the center of the molecule (602, 603, 610 and 612, nomenclature according to [78]) accommodate Chl a in all antenna complexes, with Chls 602-603 absorbing around 675 nm and Chl 610-612, absorbing around 680 nm, thereby representing the lowest energy state of the system [92,94]. On the other hand, the domain including helix C has a higher tendency to coordinate Chl b [92,97], although the occupancy of some of the sites by either Chl a or Chl b varies for the different complexes and it has been suggested that this difference is mainly related to be possibility/impossibility for the formyl group of Chl b to form H bonds [96], thus stabilizing the Chl b binding. While the L1 site of all complexes coordinates lutein, the L2 site accommodates lutein in LHCII and CP26, and violaxanthin in CP29 and CP24.…”
Section: Structure Of the Antenna Complexes Of Photosystem IImentioning
confidence: 99%
See 1 more Smart Citation
“…For most analyses this is not a problem, as the apoprotein does not contain pigments and thus does not interfere with the functional measurements. However, in case it is necessary to fully remove the apoprotein from the fraction containing the reconstituted complex (for example, to calculate the pigment to protein stoichiometry), an anionic exchange column can be used (see Passarini et al 2009 29 for details).…”
mentioning
confidence: 99%
“…The importance of different protein domains on the stability and folding of the complexes, or their involvement in the protein-protein interactions, have been determined by truncating the apoprotein or performing random mutagenesis 8,[41][42][43][44] . Single amino acid residues important for the coordination of different pigments can be altered through site-directed mutagenesis in order to analyze the properties of individual pigments or assess their contribution to the function and stability of the complex 10,28,29,[45][46][47][48][49][50][51][52] . Figure 6 shows reconstituted Lhcb4 (CP29) with a mutation of the histidine at position 216 53 .…”
mentioning
confidence: 99%